Answer:
2x + 3y = 6
Step-by-step explanation:
2x + 3y = 6
-2x. -2x
3y/3 = -2x + 6/3
Y = -2/3x + 2
Answer:
Coefficient
Explaination:
I just know
Answer:
A
Step-by-step explanation:
Hope this helps
stay safe:)
brainliest is appreciated :)))
Answer:
1. $361800
Step-by-step explanation:
Given,
principle balance=$670
interest rate=8%
A= Final amount
P= initial Principal balance
r= interest rate
n= number of times interest applied per time period
t= number of times period elapsed
compound interest formula,
Therefore the Present value is $361800
Answer:
-28
Step-by-step explanation:
(-5)(6) + (-6) ÷ (-3) =
-30 + (-6) ÷ (-3) =
-30 + 2 =
-28
<em>Hope that helps! :)</em>
<em></em>
<em>-Aphrodite</em>